Sex Differences in Neuropsychological Test Performance in Alzheimer's Disease and the Influence of the ApoE Genotype. (April 2018) - Tensil, Maria; Hessler, Johannes B.; Gutsmiedl, Maria; Riedl, Lina; Grimmer, Timo; Diehl-Schmid, Janine
Abstract : Background: Only few studies exist reporting sex differences in the Alzheimer disease (AD) patients regarding cognitive profile, brain damage, and risk factors. The present study investigated the influence of sex in combination with the Alzheimer risk allele, ε4-allele of apolipoprotein E, on cognitive performance. Materials and Methods: We examined the effect of sex and ApoE genotype on a range of neuropsychological markers from the German version of the Consortium to Establish a Registry in Alzheimer's Disease Neuropsychological Battery in a monocentric study of 399 AD patients. Results: Male patients had significantly more years of school and occupational education compared with women. Male AD patients outperformed female patients in tasks of object naming, constructional praxis, and constructional praxis recall. There was no statistically significant interaction effect between sex and ε4-allele of apolipoprotein E for any of the examined variables. Conclusions: The superiority of healthy men compared with women in tasks of object naming, constructional praxis, and visual memory seems to remain stable when people develop AD, indicating larger cognitive reserves in men. In contrast, findings that cognitively healthy women outperform men in tests of verbal memory and verbal fluency are not stable in AD. Further studies are needed to gain insight in the reasons for sex differences.